Direct and Intestinal Epithelial Cell-Mediated Effects of TLR8 Triggering on Human Dendritic Cells, CD14+CD16+ Monocytes and γδ T Lymphocytes - Angelini, Costanza; Varano, Barbara; Puddu, Patrizia; Fiori, Maurizio; Baldassarre, Antonella; Masotti, Andrea; Gessani, Sandra; Conti, Lucia (Frontiers in Immunology, 2017)
Toll-like receptor (TLR)7/8 plays a crucial role in host recognition/response to viruses and its mucosal expression directly correlates with intestinal inflammation. The aim of this study was to investigate the role of TLR7/8 stimulation of intestinal epithelium in shaping the phenotype and functions of innate immunity cell subsets, and to define direct and/or epithelial cell-mediated mechanisms of the TLR7/8 agonist R848 immunomodulatory activity. We describe novel, TLR8-mediated, pro- and anti-inflammatory effects of R848 on ex-vivo cultured human blood monocytes and gamma delta T lymphocytes, either induced by direct immune cell stimulation or mediated by intestinal epithelial cells. Apical stimulation with R848 led to its transport across normal polarized epithelial cell monolayer and resulted in the inhibition of monocyte differentiation toward immunostimulatory dendritic cells and Th1-type response. Furthermore, gamma delta T lymphocyte activation was promoted following direct exposure of these cells to the agonist. Conversely, a selective enrichment of the CD14+CD16+ monocyte subpopulation was observed, which required a CCL2-mediated inflammatory response of normal epithelial cells to R848. Of note, a TLR-mediated activation of control gamma delta T lymphocytes was promoted by inflamed intestinal epithelium from active Crohn’s disease patients. This study unravels a novel regulatory mechanism linking the activation of the TLR8 pathway in intestinal epithelial cells to the monocyte-mediated inflammatory response, and highlights the capacity of the TLR7/8 agonist R848 to directly enhance the activation of gamma delta T lymphocytes. Overall these results expand the range of cell targets and immune responses controlled by TLR8 triggering that may contribute to the antiviral response, to chronic inflammation, as well as to the adjuvant activity of TLR8 agonists, highlighting the role of intestinal epithelium microenvironment in shaping TLR agonist-induced responses.